Engineering of TeO(2)-ZnO-BaO-Based Glasses for Mid-Infrared Transmitting Optics - Linganna, Kadathala (Materials (Basel), 2020)
In this paper, the glass systems, TeO(2)–ZnO–BaO (TZB), TeO(2)–ZnO–BaO–Nb(2)O(5) (TZB–Nb) and TeO(2)–ZnO–BaO–MoO(3) (TZB–Mo), were fabricated by the traditional melt-quench protocol for use as mid-infrared (mid-IR) transmitting optical material. The effect of Nb(2)O(5) and MoO(3) on the key glass material properties was studied through various techniques. From the Raman analysis, it was found that the structural modification was clear with the addition of both Nb(2)O(5) and MoO(3) in the TZB system. The transmittance of studied glasses was measured and found that the optical window covered a region from 0.4 to 6 μm. The larger linear refractive index was obtained for the Nb(2)O(5)-doped TZB glass system than that of other studied systems. High glass transition temperature, low thermo-mechanical coefficient and high Knoop hardness were noticed in the Nb(2)O(5)-doped TZB glass system due to the increase in cross-linking density and rigidity in the tellurite network. The results suggest that the Nb(2)O(5)-doped TZB optical glasses could be a promising material for mid-infrared transmitting optics.